New results on mass measurements of stored neutron-rich nuclides in the element range from Pt to U with the FRS-ESR facility at 360–400 MeV/u - Chen, L.; Plaß, W.R.; Geissel, H.; Knöbel, R.; Kozhuharov, C.; Litvinov, Yu.A.; Patyk, Z.; Scheidenberger, C.; Siegień-Iwaniuk, K.; Sun, B.; Weick, H.; Beckert, K.; et al. (Nuclear physics. A, 2012)
Masses of 238U projectile fragments have been measured with time-resolved Schottky Mass Spectrometry (SMS) at the FRS-ESR facility at GSI. The exotic nuclei were created in the production target at the entrance of the fragment separator FRS, spatially separated in flight and injected into the storage-cooler ring ESR at about 70% light velocity. This means the ions were mainly bare or carried only a few electrons, e.g., the population of Li-like ions was below 1% for Pt fragments. Accurate new mass values of 33 neutron-rich, stored exotic nuclei in the element range from platinum to uranium have been obtained for the first time. In total more than 150 nuclides including references with well-known masses have been covered in this large-area SMS measurement. A novel data analysis has been applied which reduces the systematic errors by taking into account the velocity profile of the cooler electrons and the residual ion-optical dispersion in this part of the storage ring. The experiment, the data analysis, and the mass values are presented. The experimental data are compared with theoretical predictions demonstrating systematic deviations of up to 1500 keV from modern mass models.